Will they listen to me? Investigating the utilization of audio feedback in higher education - Saputra, Dwi Bayu; Arianto, M. Affandi; Saputra, Eko (Studies in English Language and Education, 2023)
Many studies have discussed the importance of technology in delivering feedback to students assignments since its deployment provides convenience, timeliness, rich information, asynchronous discussion, and social presence. However, the effectiveness of audio feedback has received very scant investigation in the context of higher education in Indonesia. To fill such an empirical void, this exploratory sequential mixed method probes the students perceptions towards the use of audio feedback. Thirty-two undergraduate students from one of the public universities in Bengkulu, Indonesia, majoring in Early Childhood and Studies and taking English as a compulsory subject, participated in this study. Three data collection techniques were deployed to triangulate the data. A questionnaire was distributed to examine students perceptions of audio feedback, followed by a freeform writing and semi-structured interview to draw more pictures of the students experiences of this feedback mode. The results show that even though all participants in this study had never received this type of feedback, most participants had positive perceptions of using audio feedback. They mentioned they got thorough, detailed, and personal feedback, so they felt engaged in the learning processes. This finding is expected to enrich the knowledge of the effectiveness of audio feedback and to encourage eager teaching practitioners to use it in their teaching processes, as it could increase students engagement in the learning process.